Residue of Pesticides in Fruits, Vegetables, and Their Management in Ethiopia - Yohannes Gelaye; Belete Negash (Journal of Chemistry)
In Ethiopia, using pesticides to manage pests in the growing of fruits and vegetables is a standard practice. Various classes of pesticides have been approved to combat pests, but the majority of those in use now are outdated broad-spectrum insecticides with significant residual effects on crops of freshly eaten fruits and vegetables. This review reveals that Ethiopia’s assessment of the residual pesticide level in fruits and vegetables has been lacking. According to the reviewed literature, crops that are often treated with pesticides in many countries have significant residual pesticide levels. However, Ethiopia has not adequately reported on this issue. Furthermore, due to a lack of knowledge regarding the impact of pesticide residues on human health, Ethiopians frequently use pesticides improperly to control pests in fruits and vegetables. The majority of consumers eat their fruits and vegetables unprocessed, without washing or cooking them first. To reduce the risk of pesticide residues in fruits and vegetables for consumer safety and to battle the health effects of toxic chemicals in humans, monitoring pesticide residues and raising awareness about the adverse effects of pesticides on humans are urgently needed. Before they may be registered and sold, pesticide residues in fruits and vegetables as well as in the environment must also undergo proper testing and evaluation. New pesticide generations that have fewer side effects on fruits and vegetables must also be developed. By washing, peeling, canning, or boiling fruits and vegetables before consumption, the detrimental effects of pesticide residues on human health can be minimized.